Ảnh hưởng của trải nghiệm hợp kênh đến trung thành và kết dính thương hiệu thông qua tình yêu thương hiệu: Mô hình tác động trực tiếp và gián tiếp - Nguyễn Hữu , Khôi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The role of omnichannel experience and its underlying mechanisms through which this variable influences loyalty and stickiness have received little attention. Drawing on engagement theory, this study proposes a model comprising both direct and indirect effects among omnichannel experience, brand love, including brand intimacy and brand passion, and positive brand outcomes, encompassing loyalty and stickiness. Hypothesis testing using partial least squares structural equation modeling (PLS-SEM) with a sample of 355 consumers in Khanh Hoa supports all proposed hypotheses. Accordingly, the study provides deeper insights into the significant contribution of omnichannel experience in fostering consumer brand loyalty and stickiness, as well as clarifying the role of brand love as the mechanism connecting these variables. Based on the research results, theoretical implications regarding the relationships among the variables are discussed, and managerial implications are proposed to enhance positive omnichannel experiences and brand love
Keywords: Brand passion; Brand intimacy; Brand love; Brand Stickiness; Loyalty; Omnichannel experience